Proceedings of the 1st International Conference on Economics, Business, Entrepreneurship, and Finance (ICEBEF 2018) 2019
DOI: 10.2991/icebef-18.2019.148
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Perceived Organizational Support and Job Satisfaction

Abstract: Construction industries are exposed to a high competition. Such situation could affect the emloyees since organization also increase their demand in terms of long working hours, high workload, high quality standard, and lack of job security. Facing this challenges some employees might feel less satisfied and tend to come out with quick response to leave the organization. This paper aims to explore the turnover intention in constrcution industry. A questionnaire is used to collect data from 110 employees. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
1
6
3
1
Order By: Relevance
“…The results of this study showed perceived organizational support and self-efficacy had a positive and significant effect on work engagement. The results support research conducted earlier by Hasnida et al (2019), which stated that perceived organizational support and self-efficacy positively affect work engagement. Similarly, research conducted by Sulistyo & Suhartini (2019) states the same thing and gives the opinion that employees with a good perceived organizational support will give a positive attitude towards the work, as well as those who have good self-efficacy will show confidence when facing difficulties in doing work in various situations and conditions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of this study showed perceived organizational support and self-efficacy had a positive and significant effect on work engagement. The results support research conducted earlier by Hasnida et al (2019), which stated that perceived organizational support and self-efficacy positively affect work engagement. Similarly, research conducted by Sulistyo & Suhartini (2019) states the same thing and gives the opinion that employees with a good perceived organizational support will give a positive attitude towards the work, as well as those who have good self-efficacy will show confidence when facing difficulties in doing work in various situations and conditions.…”
Section: Discussionsupporting
confidence: 89%
“…The reality of the survey results for perceived organizational support, self-efficacy, and work engagement has differences with the results of previous research conducted by Hasnida et al (2019), Sulistyo & Suhartini (2019), and others which states that perceived organizational support and self-efficacy has a positive and significant effect on work engagement. This indicates an irregularity between the two results.…”
Section: Introductioncontrasting
confidence: 84%
“…Therefore, healthcare settings must take cognisance of the employee’s perceptions of the work situation including the characteristics of the organisation to create an organisational climate that has a direct relationship with the employees. Several studies showed that employees who are supported by their organisation are satisfied with their job and display positive behaviour and commitment to organisational norms (Ayuningtias et al 2019 ; Günay 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…In their study with employees of a German market research company, Jiménez et al (2017) have determined that JS has a mediating effect on the effect of job insecurity on TI. In their study with employees in the construction sector of Indonesia, Ayuningtias et al (2019) have reported that JS has a mediating effect on the effect of POS on TI. Thus, three hypotheses regarding the mediating effect of JS were developed as follows:…”
Section: The Mediating Role Of Job Satisfactionmentioning
confidence: 98%
“…In other words, POS improves employees' sense of belonging and fullfils their socio-emotional needs, increasing JS and decreasing TI (Kurtessis et al, 2017(Kurtessis et al, : 1877. Studies show that employees with higher POS have higher JS and lower TI (Rhoades & Eisenberger, 2002;Knapp et al, 2017;Kurtessis et al, 2017;Rai, 2017;Ayuningtias et al, 2019). Thus, the following hypotheses were developed: H 6 : POS has a positive effect on JS.…”
Section: The Relationship Between Pos Job Satisfaction and Turnover Intentionmentioning
confidence: 99%